Effect of uniaxial pressure on charge transport in the layered manganite La1.25Sr1.75Mn2O7 - Arumugam, S; Mydeen, K; Manivannan, N; Vanji, M; Prabhakaran, D; Boothroyd, A; Sharma, R; Mandal, P (2006)
The effect of uniaxial pressure on resistivity along the ab plane (ρab) and c axis (ρc) in single crystals of bilayer manganite La1.25 Sr1.75 Mn2 O7 has been investigated. A prominent finding is the asymmetric role of pressure on charge transport phenomenon. With increasing pressure along the c axis, ρab decreases and the metal-insulator (MI) transition temperature shifts towards higher temperature at the rate of 46 K GPa. In contrary to this, ρc increases and the MI transition temperature decreases with increasing pressure along the ab plane. The resistivity ratio ρc ρab is quite large, increases with pressure, and shows a peak at around the MI transition. We believe that the unusual behavior of transport properties is related to the Mn-O-Mn linkage between MnO2 layers and the spin reorientation from the c axis to the basal plane and vice versa with pressure. © 2006 The American Physical Society.